Role of Entrepreneur during Pandemic in India - Hitendra Bargal, Vinod Kumar Patel, Ashish Sharma (International Journal of Advanced Science and Technology, 2020)
Purpose – The outburst of COVID-19 and the non-availability of medicines, and proper safety gears, all eyes look towards the entrepreneur to come up with the solution, as an entrepreneur have the bunch of researchers to look deep into the problem and come up with the commercialized product. As they use their channel to distribute the medicines, essentials goods, safety kits, and testing kits in bulk and they can produce the safety items in large quantities.